Carbon and energy use reporting for government office buildings in Putrajaya - Wang, Tze Wee (2017)
The Malaysian Government has announced to develop Putrajaya as a pioneer Green Township in Malaysia. Policy to reduce the carbon footprint is stipulated in the Putrajaya Structure Plan 2025. Major carbon reduction is expected to be contributed by the building sector, particularly non-residential buildings due to their highest emissions volume and increasing emission trends. However, carbon reduction possibilities have yet to be identified and building sector’s stakeholder engagement in emission mitigation remained uncertain. Carbon and energy use reporting is one of the mechanisms increasingly implemented by cities in developed nations but not commonly practiced in Malaysia. This research is to examine the application of carbon and energy use reporting in reducing emissions in Putrajaya’s government office buildings. Literature reviews suggest that implementation of reporting programme should consider six (6) common driving factors (regulatory compliance, energy cost savings, leadership, enhancing reputation, fostering relationship with stakeholders and environmental awareness), key elements in reporting and implementation approach used in the empirical cases. This study has carried out interviews with questionnaire with all 29 facility managers of existing government office buildings in Putrajaya, to investigate the current reporting status, practices, their agreement and expectation towards reporting programme. The survey data were analysed using frequency analysis and chi-square test for independence to test the association between variables. The survey results showed that 82.8% of the facility managers conduct carbon and energy use reporting. This reporting status has no significant association with their company size (p-value=0.371>0.05). Regulatory compliance and fostering relationship with stakeholders are the key driving factors for facility managers’ engagement in this reporting activity. Reporting obligation was based on contract scopes and stakeholders’ request. Carbon abatement potential through benchmarking against other similar office buildings and public disclosure of building performance are not widely conducted, with less than 1/3 of facility managers practicing this. Future mandatory reporting was generally agreed by facility managers. This agreement has no significant association with their working experiences in Putrajaya (p-value=1.00>0.05). Based on the findings, recommendations have been proposed to improve the current reporting practice and future expansion to the whole building sector in Putrajaya, so that Government can lead by example to effectively encourage this new practice.